Use of Photovoice Methods in Research on Informal Caring: A Scoping Review of the Literature - Ilagan, Chloe; Akbari, Zahra; Sethi, Bharati; Williams, Allison (Journal of Human Health Research, 2020)
The purpose of this scoping review was to examine the use of Photovoice in caring research. The review assessed the existing literature using the Arksey and O’Malley scoping review methodology. Database searches of relevant literature published worldwide between 1997–2019 yielded 25 articles in the English language that were included in this review. The authors summarized thematic findings. Three themes emerged from data analysis: 1) strengths of using Photovoice; 2) challenges of using Photovoice, and; 3) methodological complexities in Photovoice studies. The small number of studies included in the review (n=25) indicate the limited use of Photovoice in caring research, reflecting missed opportunities for action-oriented research. The scoping review recommends ways that researchers can better address the needs of carers using Photovoice, particularly as a tool for knowledge translation, advocacy, and empowerment.
Keywords: caring; Photovoice; scoping review; participatory action research